WNT inhibitor SP5-mediated SERPING1 suppresses lung adenocarcinoma progression via TSC2/mTOR pathway - Yefeng Shen; Xiaofeng Dong; Xujia Li; Zhiyuan Shi; Tingting Shao; Junlan Jiang; Jian Song (Cell Death and Disease)
Abstract The long-term outlook for patients grappling with lung cancer (LC) remains bleak, with lung adenocarcinoma (LUAD) emerging as the most predominant histological subtype. Our Mendelian randomization (MR) investigation spotlighted that heightened levels of the circulating protein serpin peptidase inhibitor family G1 (SERPING1) substantially mitigated LC risk. The fusion of multi-omics strategies unveiled that SERPING1 exhibited diminished expression in LUAD patients compared to healthy individuals both in tissues and serum, with LUAD individuals showcasing elevated SERPING1 expression demonstrating improved prognoses. Furthermore, SERPING1 expression exhibited a robust correlation with the efficacy of immunotherapy. Through meticulous in vivo and in vitro analyses, we unraveled that SERPING1 impeded the proliferation, migration, invasion and wound healing of LUAD cells via the tuberous sclerosis 2 (TSC2)/mammalian target of rapamycin (mTOR) pathway. Mechanistically, WNT inhibitor- Specificity Protein (SP5) was delineated as facilitator of SERPING1 transcription by binding to the SERPING1 gene promoter. Intriguingly, aside from the association between SERPING1 and systolic blood pressure, glycosylated hemoglobin (HbA1c), type I diabetes, no discernible link between SERPING1 overexpression and heightened risks of other cardiometabolic conditions and diseases was evident. In summary, SERPING1 emerges as a novel tumor suppressor gene and SP5/SERPING1/TSC2 is a promising therapeutic target in the context of LUAD.